2022
DOI: 10.1161/jaha.121.023839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Upright Versus Supine Position on Resting and Exercise Hemodynamics in Patients Assessed for Pulmonary Hypertension

Abstract: Background The aim of the present work was to study the influence of body position on resting and exercise pulmonary hemodynamics in patients assessed for pulmonary hypertension (PH). Methods and Results Data from 483 patients with suspected PH undergoing right heart catheterization for clinical indications (62% women, age 61±15 years, 246 precapillary PH, 48 postcapillary PH, 106 exercise PH, 83 no PH) were analyzed; 213 patients (main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…This is likely explained by prolonged recumbent state during infusion. Higher venous return in supine position may increase pulmonary arterial pressure 13 . Similarly, TAPSE decreased in the placebo group, possibly explained by recumbent haemodynamics and lower demands at rest.…”
Section: Discussionmentioning
confidence: 93%
“…This is likely explained by prolonged recumbent state during infusion. Higher venous return in supine position may increase pulmonary arterial pressure 13 . Similarly, TAPSE decreased in the placebo group, possibly explained by recumbent haemodynamics and lower demands at rest.…”
Section: Discussionmentioning
confidence: 93%
“…[16][17][18] When the decrease in SV is not compensated by a proportional increase in heart rate, the CO (CO = SV × HR) is therefore reduced, which also lessens the pulmonary pressures. 15,19 Conversely, the supine position enhances venous return by mobilization of blood from the lower extremities to the core circulation, which increases the ventricular preload, resulting in a higher CO. 8,9 A systematic review of healthy subjects reported that the mPAP (14.8 ± 2.9 mmHg vs. 13.8 ± 3.6 mmHg) and CO (6.6 ± 1.7 vs. 5.5 ± 1.1 L/min) at rest, as well as the mPAP (24.9 ± 7.1 mmHg vs. 22.1 ± 5.0 mmHg) and CO (15.8 ± 3.2 vs. 14.7 ± 2.9 L/min) during submaximal exercise were slightly lower in the upright than supine position. 15 The reduction in mPAP in the sitting position was more pronounced than expected as we included patients with preload insufficiency and postcapillary PH.…”
Section: Discussionmentioning
confidence: 99%
“…However, exercise above 60 W in either position did not change hemodynamic classifications in the majority of cases, and previously published studies on the same topic, the average workload achieved was even lower. 8 Lastly, there is no established definition of preload insufficiency, particularly in the absence of complimentary iCPET that could have provided oxygen consumption at different stages (to calculate Fick CO and peak CO percentage of predicted). 3,6 Body position significantly influences hemodynamics at rest and with exercise; however, the mPAP/CO and PAWP/CO were not positionally affected.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary haemodynamics are highly influenced by body position. Resting mPAP, PAWP and CO are lower, while heart rate, TPR and PVR are increased in the upright position, as compared to the supine position [ 17 , 23 ]. In the supine position, TPR and PVR decrease moderately during exercise, while this is more prominent in the upright position [ 5 ].…”
Section: Methodological Details For the Correct Interpretation Of Exe...mentioning
confidence: 99%